Association of HIV and Opportunistic Infections With Incident Stroke: A Nationwide Population-Based Cohort Study in Taiwan. (1st February 2017) - Yen, Yung-Feng; Chen, Marcelo; Jen, Ian; Lan, Yu-Ching; Chuang, Pei-Hung; Liu, Yen-Ling; Lee, Yun; Chen, Yi-Ming Arthur
Abstract : Background: HIV-associated vasculopathy and opportunistic infections (OIs) might cause vascular atherosclerosis and aneurysmal arteriopathy, which could increase the risk of incident stroke. However, few longitudinal studies have investigated the link between HIV and incident stroke. This cohort study evaluated the association of HIV and OIs with incident stroke. Methods: We identified adults with HIV infection in 2000–2012, using the Taiwan National Health Insurance Research Database. A control cohort without HIV infection, matched for age and sex, was selected for comparison. Stroke incidence until December 31, 2012 was then ascertained for all patients. A time-dependent Cox regression model was used to determine the association between OIs and incident stroke among patients with HIV. Results: Among a total of 106, 875 patients (21, 375 patients with HIV and 85, 500 matched controls), stroke occurred in 927 patients (0.87%) during a mean follow-up period of 5.44 years, including 672 (0.63%) ischemic strokes and 255 (0.24%) hemorrhagic strokes. After adjusting for other covariates, HIV infection was an independent risk factor for incident all-cause stroke [adjusted hazard ratio (AHR) 1.83; 95% confidence interval (CI): 1.58 to 2.13]. When the type of stroke was considered, HIV infection increased the risks of ischemic (AHR 1.33; 95% CI: 1.09 to 1.63) and hemorrhagic stroke (AHR 2.01; 95% CI: 1.51 to 2.69). The risk of incident stroke was significantly higher in patients with HIV with cryptococcal meningitis (AHR 4.40; 95% CI: 1.38 to 14.02), cytomegalovirus disease (AHR 2.79; 95% CI: 1.37 to 5.67), and Penicillium marneffei infection (AHR 2.90; 95% CI: 1.16 to 7.28). Conclusions: Patients with HIV had an increased risk of stroke, particularly those with cryptococcal meningitis, cytomegalovirus, or P. marneffei infection. Abstract : Supplemental Digital Content is Available in the Text.